A kinetic, isotherm adsorption, and thermodynamic study of Congo red coagulation using Leucaena crude extract as natural coagulant. Issue 6 (25th May 2022) - Kristianto, Hans; Manurung, Natasa; Wardhani, Irene Kusuma; Prasetyo, Susiana; Sugih, Asaf K.; Arbita, Ariestya A.
Abstract: The utilization of various natural resources as coagulant to treat various types of water and wastewater has seen considerable growth in recent years. The coagulation mechanism of natural coagulant is commonly charge neutralization followed by adsorption during the floc growth. However, due to lack of information, further investigation into the nature of the coagulation mechanism is needed. In this study, the coagulation of Congo red synthetic wastewater using crude leucaena extract was investigated at various initial Congo red concentrations (50–100 mg/L) and coagulation temperatures ranging from 30 to 50 °C. Furthermore, the nature of coagulation was investigated using various adsorption isotherms (the Langmuir, Freundlich, Temkin, and Brunauer-Emmet-Teller models) and kinetic models (pseudo-first, pseudo-second, Elovich, and intraparticle models). It was found that the Congo red concentrations, coagulation temperatures, and their interaction are significant to the dye removal. The sedimentation was well described by the pseudo-second order kinetic model, and the coagulation process followed the Langmuir isotherm. This indicates that the coagulation process involved chemisorption with monolayer formation on the coagulant. Moreover, the thermodynamic study shows that the coagulation was both endothermic and spontaneous. HIGHLIGHTS: Crude protein was extracted from Leucaena leucocephala . The Congo red coagulation followed Langmuir isotherm model. The settling kinetic followed the pseudo-second order kinetic model. The coagulation using leucaena crude extract was endothermic and spontaneous nature. Graphical Abstract